Global experience with medical cannabis use: indications and safety profile (literature review) - Kaidash , S.P.; Sliesarchuk , V.Yu.; Sokolova, K.V.; Potapova , T.M. (Medicni Perspektivi, 2025)
Over the past decades, medical cannabis has received official recognition in more than 40 countries around the world, including Germany, Canada, Italy, and Israel. Medical cannabis is considered a potentially effective remedy for incurable conditions accompanied by pain, spasms, or nausea. Despite its relative safety compared to opioids, the issue of side effects remains relevant. The aim of the study was to systematize information on the main pharmacological properties of medical cannabis and its bioactive components, available dosage forms and medically approved cannabis-based drugs, as well as analyze the evidence base for assessing the effectiveness of medical cannabis in various pathological conditions, taking into account potential risks and safety of use in clinical practice. To achieve the aim of the study, a search for scientific publications was carried out using the queries: medical marijuana, cannabis, cannabinoids, names of medical cannabis drugs, names of cannabinoids in the PubMed, Scopus and Google Scholar databases (2005-2025). 8254 results were obtained for the query. The exclusion criteria were: publications that did not meet the purpose of the review; language of publications (except Ukrainian, English); annotations that did not contain complete information about the results of the studies; publications with closed access. 44 publications were selected for analysis. The article analyzed clinical conditions in which the use of cannabis may be potentially beneficial (mental disorders (post-traumatic stress disorder, anxiety, depression), pain, drug addiction, diseases of the central nervous system and gastrointestinal tract). The safety of medical cannabis is highlighted: risks of addiction, neuro- and cardiotoxicity, psychotic reactions, side effects and features of using by vulnerable groups. Despite the growth of therapeutic use, the evidence base for clinical benefit remains incomplete, and undesirable effects limit its use. The choice of form and route of administration should be adapted to the individual needs of the patient. Thus, the analysis of the literature confirms the significant potential of medical cannabis in the treatment of various diseases, but the safety of its use requires further research.